PELATIHAN METODE ALI BAGI GURU UNTUK PENINGKATAN PEMBELAJARAN AL-QUR'AN DI DESA SENGGRONG, BOYOLALI - Astoko, Dudi Budi; Subando, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This training program aims to assess the effectiveness of the Ali method in improving the quality of Qur'an learning for TPQ teachers throughout Senggrong Village, Andong District, Boyolali Regency, by integrating the Ali method into their teaching. The approach used in this program combines Participatory Action Research (PAR) and Workshop-Based Training, involving local TPQ teachers as both training participants and practitioners in applying the Ali method. The activities include training sessions, discussions, demonstrations, and intensive mentoring to teach effective and enjoyable methods for learning to read the Qur'an. The training has shown a positive impact, with 50% of participants stating that it was highly beneficial and the remaining 50% finding it moderately helpful in enhancing their Qur'an teaching competence. However, some challenges remain, such as limited initial understanding of the Ali method, time constraints in teaching, and participants' unfamiliarity with this new approach. Overall, the training has successfully improved the quality of Qur'an instruction, but continuous support is needed to ensure the optimal implementation of the Ali method in the future.